Isu Lesbian Gay Biseksual Transgender (LGBT) Pada Media Online - Sakti Dwi Jaya; Subhan Afifi; Reny Triwardani (Jurnal Paradigma, 2018)
This study discusses the framing analysis of news about the issue of lesbian, gay, bisexual, and transgender (LGBT) on Online Media Jogja (January-March 2016).